BERMITRA DI MASA PANDEMI (Studi Kasus Pola Kemitraan Perusahaan – Petani Di Kec. Ciwidey, Kab. Bandung) - Nugraha, Adi; Heryanto, Mahra A. (Universitas Galuh, 2023)
Partnerships in the agricultural sector should provide benefits for the partnering parties, especially farmers with small-scale farming conditions that have limited capital, narrow land tenure, and use of simple agricultural tools. This study aims to describe the pattern of partnerships that have been established between companies and plasma farmers in Ciwidey District, Bandung Regency, and to find out the benefits that plasma farmers and companies receive after carrying out partnership activities, especially in dealing with the COVID-19 pandemic. This study uses a qualitative design with a case study approach. Data were obtained through in-depth interview techniques conducted with key informants consisting of partner farmers and company representatives. The results of this study indicate that the two parties use the plasma nucleus pattern partnership system, their conditions are better after establishing a partnership relationship because they can increase production and increase income for the company and welfare for partner farmers. In addition, there are other benefits to be gained from this partnership, namely networking for farmers and companies to increase production volume by building relationships in several regions.